An analysis of conservation guideline for old shophouses case study: Ipoh City and Little India, Singapore / Ahmad Mazlan Mahayudin - Mahayudin, Ahmad Mazlan (2001)
There is much effort and roles by local authorities to develop and maintain their city. One of it is conservation and preservation of historical heritage in the city such as detached buildings and old shophouses that have historical value. The conservation of detached buildings is most regular done at the same time as the conservation of old shophouses is actively being progressed. Hence, the preservation of old shophouses is mostly retained the front structure; the interior of the building has major changing to new functional buildings. Therefore, the conservation guidelines are a way to control the old shophouses. Furthermore, the local authority should take an action clearly neither to prevent new developments for city or destroying the historical value in the city.